2017
DOI: 10.1136/rmdopen-2017-000436
|View full text |Cite
|
Sign up to set email alerts
|

Nardilysin is involved in autoimmune arthritis via the regulation of tumour necrosis factor alpha secretion

Abstract: ObjectiveTumour necrosis factor alpha (TNF-α) plays an important role in rheumatoid arthritis (RA). TNF-α is synthesised as a membrane-anchored precursor and is fully activated by a disintegrin and metalloproteinase 17 (ADAM17)-mediated ectodomain shedding. Nardilysin (NRDC) facilitates ectodomain shedding via activation of ADAM17. This study was undertaken to elucidate the role of NRDC in RA.MethodsNRDC-deficient (Nrdc–/–) mice and macrophage-specific NRDC-deficient (NrdcdelM) mice were examined in murine RA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…To address the importance of MEF2C in osteoclast-mediated pathological bone resorption, we tested the effects of MEF2C deficiency on bone loss in K/BXN serum-induced arthritis. 35 K/BxN serum was administrated intra-peritoneally on day 0 and day 2 (Fig. 7a ).…”
Section: Resultsmentioning
confidence: 99%
“…To address the importance of MEF2C in osteoclast-mediated pathological bone resorption, we tested the effects of MEF2C deficiency on bone loss in K/BXN serum-induced arthritis. 35 K/BxN serum was administrated intra-peritoneally on day 0 and day 2 (Fig. 7a ).…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported that NRDC levels were increased in the synovial fluid of patients with rheumatoid arthritis (31). NRDC in macrophages regulates arthritis via the control of TNFa secretion because the macrophage-specific deletion of NRDC markedly ameliorated arthritis (31). We also demonstrated that inflammatory cells infiltrating the infarcted myocardium strongly express NRDC (25).…”
Section: Discussionmentioning
confidence: 62%
“…Another possible source of serum NRDC is inflammatory cells adjacent to tumors. We recently reported that NRDC levels were increased in the synovial fluid of patients with rheumatoid arthritis (31). NRDC in macrophages regulates arthritis via the control of TNFa secretion because the macrophage-specific deletion of NRDC markedly ameliorated arthritis (31).…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Moreover, we have recently proposed the possible clinical use of serum NRDC levels as a biomarker for several clinical settings. [24][25][26] For example, serum NRDC is elevated early after the onset in patients with acute coronary syndrome. 27 Here, we demonstrate that NRDC critically regulates circulatory dynamics because Nrdc −/− mice show hypotension and bradycardia.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this extracellular function as an enhancer of ectodomain cleavage, NRDC in the nucleus controls transcription as a coregulator of several transcription factors such as peroxisome proliferator‐activated receptor gamma coactivator 1‐alpha (PGC‐1α), 21 islet‐1, 22 and histone deacetylases 23,24 . Moreover, we have recently proposed the possible clinical use of serum NRDC levels as a biomarker for several clinical settings 25‐27 . For example, serum NRDC is elevated early after the onset in patients with acute coronary syndrome 28…”
Section: Introductionmentioning
confidence: 99%